2003
DOI: 10.1007/s10350-004-6579-0
|View full text |Cite
|
Sign up to set email alerts
|

Longer Time Interval Between Completion of Neoadjuvant Chemoradiation and Surgical Resection Does Not Improve Downstaging of Rectal Carcinoma

Abstract: Perioperative morbidity is not affected by longer intervals. A longer interval between completion of neoadjuvant chemoradiation and surgical resection may not increase the tumor response rate of advanced rectal cancer in this cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 17 publications
7
87
1
1
Order By: Relevance
“…Следует отметить, что в настоящее время полная регрес-сия опухоли после неоадъювантного лечения является мощным прогностическим фактором, позитивно влияю-щим на послеоперационную безрецидивную выживае-мость больных. Это подтверждается данными крупных рандомизированных исследований [21][22][23]. Все они ука-зывают на улучшение результатов лечения с увеличением ответа опухоли на предоперационную терапию [24].…”
Section: Discussionunclassified
“…Следует отметить, что в настоящее время полная регрес-сия опухоли после неоадъювантного лечения является мощным прогностическим фактором, позитивно влияю-щим на послеоперационную безрецидивную выживае-мость больных. Это подтверждается данными крупных рандомизированных исследований [21][22][23]. Все они ука-зывают на улучшение результатов лечения с увеличением ответа опухоли на предоперационную терапию [24].…”
Section: Discussionunclassified
“…This finding may prove to be of significance during planning of surgical treatment. The percentage of patients with "T-downstaging" in the group submitted to long-term radiotherapy and radiochemotherapy ranged from 23/88 (26.0%) to 15/20 (75.0%) [14,17,[20][21][22][23][24]27,[34][35][36]39,[46][47][48][49]51,52] . Among patients submitted to short-term preoperative radiotherapy "T-downstaging" ranged between 10/28 (35.7%) and 44/104 (43%) [11,14,18,19] .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors studied "N-downstaging" parameter [17,20,[22][23][24][25][26]36,47] and showed its prognostic value [17] . The percentage of patients submitted to radiochemotherapy or radiotherapy with long time intervals between neo-adjuvant treatment and surgery, in which "N-downstaging" was noted, ranged from 13/26 (50.0%) to 38/42 (90.4%) [17,20,[22][23][24][25][26]36,47] . Tumor size decrease, 'sterilization' and lymph node atrophy are the classic effects of radiotherapy [20,44,45] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Moreover, some studies have failed to demonstrate an association between an increased interval before surgery and improved pCR rates. 61 meeting from the first 32 patients reported a 33 % pCR rate with over a 90 % treatment compliance rate. 63 The mature study results from both the Timing Trial and the CONTRE trial are eagerly awaited, and will no doubt provide important information for the design and conduct of future neoadjuvant rectal cancer trials.…”
Section: Optimal Timing Of Surgery?mentioning
confidence: 99%